1978
DOI: 10.1161/01.res.43.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Lung fluid exchange after uneven pulmonary artery obstruction in sheep.

Abstract: SUMMARY We studied steady state transvascular fluid and protein exchange after uneven obstruction of the pulmonary arteries. In anesthetized sheep, ventilated by positive pressure, we measured pulmonary artery and left atrial pressures, cardiac output, lung lymph flow, and lymph/plasma protein ratios. We calculated pulmonary vascular resistance. In 16 sheep we obstructed the pulmonary arteries with various microemboli or balloons in lobar arteries until pulmonary vascular resistance was 2-3 times baseline. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(38 citation statements)
references
References 35 publications
2
33
2
1
Order By: Relevance
“…Since the protein composition of lung lymph is the same as that of free interstitial fluid of the lung (Vreim et al 1976), it is possible to analyze the fluid and protein exchange through the pulmonary vasculature. The elevation of pulmonary microvascular pressure increases the transvascular fluid filtration , and pulmonary microembolism enhances the transvascular fluid and protein permeability (Ohkuda et al 1978). In the present study, irradiation did not affect pulmonary hemodynamics, but increased Qlym and LAP significantly.…”
Section: Discussioncontrasting
confidence: 49%
“…Since the protein composition of lung lymph is the same as that of free interstitial fluid of the lung (Vreim et al 1976), it is possible to analyze the fluid and protein exchange through the pulmonary vasculature. The elevation of pulmonary microvascular pressure increases the transvascular fluid filtration , and pulmonary microembolism enhances the transvascular fluid and protein permeability (Ohkuda et al 1978). In the present study, irradiation did not affect pulmonary hemodynamics, but increased Qlym and LAP significantly.…”
Section: Discussioncontrasting
confidence: 49%
“…Alternatively, pulmonary vasoconstriction may have been caused by vasoactive cytokines (Malik andvan der Zee 1977, Binder et al 1980). It is unlikely that the increase in PVR was due mechanical occlusion of the pulmonary vessels by emboli or thrombi, because blockage of more than 50% of all pulmonary arteries would be necessary to increase PVR (Dalen et al 1967, Ohkuda et al 1978.…”
Section: Discussionmentioning
confidence: 99%
“…Elegant studies using sheep have previously demonstrated that acute increases in PBF or pressure led to increased capillary filtration of protein-poor fluid and augmented clearance of lymphatic fluid (12,19,42,44,50). However, infants born with congenital cardiac defects often live with increased PBF for months or years before their defects are surgically corrected, and it remains unknown what effect this chronically increased PBF has on the function and structure of the pulmonary lymphatic system.…”
mentioning
confidence: 99%